Assessing the viability of K-Mo2C for reverse water–gas shift scale-up: molecular to laboratory to pilot scale. Issue 8 (14th July 2020) - Juneau, Mitchell; Vonglis, Madeline; Hartvigsen, Joseph; Frost, Lyman; Bayerl, Dylan; Dixit, Mudit; Mpourmpakis, Giannis; Morse, James R.; Baldwin, Jeffrey W.; Willauer, Heather D.; Porosoff, Marc D.
Abstract : K-Mo2 C/γ-Al2 O3 is a low-cost, high performance RWGS catalyst suitable for high throughput CO2 conversion into chemicals and fuels. Abstract : Conversion of CO2 to value-added chemicals and fuels is a potentially valuable route for renewable energy storage and a future CO2 -neutral economy. The first step is CO2 conversion to CO via the reverse water–gas shift (RWGS) reaction. Effluent CO can then be hydrogenated to chemicals and fuels via Fischer–Tropsch (FT) synthesis over a tandem catalyst or within a second reactor. To implement this process on an industrial scale, low-cost, scalable and highly-selective catalysts are required, prompting investigations into materials that meet these design constraints. Potassium-promoted molybdenum carbide supported on gamma alumina (K-Mo2 C/γ-Al2 O3 ) has recently been shown to be a highly active and selective RWGS catalyst in the laboratory, prompting us to investigate the viability of K-Mo2 C/γ-Al2 O3 for scale-up. In this report, laboratory-scale (∼100 mg catalyst) reactor studies are extended to the pilot-scale (∼1 kg catalyst), and viability for scale-up is tested further with density functional theory (DFT) calculations, detailed characterization and reactor experiments under a range of temperatures (300–600 °C) and flow conditions. The pilot-scale experiments illustrate K-Mo2 C/γ-Al2 O3 is a highly active and selective catalyst (44% CO2 conversion, 98%+ CO selectivity at GHSV = 1.7 L kg −1 s −1 and T = 450 °C) that exhibits no signs of deactivation for over 10 days on stream. Together, experiments across the molecular, laboratory and pilot scales demonstrate that K-Mo2 C/γ-Al2 O3 is an economically-viable RWGS catalyst with promising future applications in the US Naval Research Laboratory's seawater-to-fuel process, downstream methanol synthesis and FT.